Masking the problem - Human errors in qualitative respiratory equipment fit testing - Long, Karen M (Cranfield University, 2022)
Respiratory protective devices are designed to protect wearers from inhalation hazards in the workplace. The performance of tight-fitting devices relies on a good face-to-facepiece seal, and this is tested through a prescribed procedure known as a ‘fit test’ which provides an assessment of face seal leakage using either a quantitative or qualitative detection method. Numerous anecdotal reports exist about human errors in workplace application of the qualitative fit test method, but published research is limited to laboratory-based studies. This thesis provides the first investigation of real-world human errors in qualitative fit testing and proposes measures to improve the reliability of this widely used fit test method. Through an extensive literature review, the study examines the multi-faceted body of current research and identifies a major research gap in the knowledge pertaining to human errors. An assessment of the prevalence and sources of human errors in qualitative fit testing is conducted through secondary analysis of data acquired during Fit2Fit practical assessments. Findings provide information about the types of errors made by real-world fit testers, trends over time, and differences between Fit2Fit accredited and non-accredited fit testers. Through a theoretical analysis of the fundamental method principles, this thesis postulates a set of ‘critical errors’ which have the potential to undermine the reliability of the test. An empirical assessment of the impact of critical errors is conducted through a series of aerosol concentration studies and live shortened fit tests. When these impacts are applied to secondary data of errors made by real-world fit testers, this thesis offers the first estimate of a workplace (Beta) error value for this fit test method. Through examination of current control measures, this thesis highlights gaps in current resources, and proposes a set of engineering and administrative solutions which aim to address critical errors and improve workplace safety.
Keywords: Facepiece; face seal; leakage; taste test; hood test; Bitrex